Stress engineering for reducing the injection current induced blue shift in InGaN-based red light-emitting diodes. Issue 12 (17th February 2021) - Yao, Weizhen; Wang, Lianshan; Meng, Yulin; Yang, Shaoyan; Liu, Xianglin; Niu, Huidan; Wang, Zhanguo
Abstract : Red LEDs with a small blue shift are fabricated by using a stress engineering strategy through the growth of the pre-stained InGaN layer and dual-wavelength QWs on a cone-shape patterned sapphire substrate. Abstract : Long visible light-emitting diodes (LEDs) have been proven promising in solid-state lighting covering all visible wavelengths. However, the efficiency of LEDs with high indium content in InGaN multiple quantum wells (MQWs) substantially decreases in long wavelengths. Herein, we present the growth of a pre-strained InGaN layer and dual-wavelength LED structures on cone-shape-patterned sapphires by metal–organic chemical vapor deposition. V-pits can thus be formed within the pre-strained layer and red QWs due to the stress relaxation. This enhances the incorporation of indium in the InGaN/GaN MQWs so that red LEDs can be fabricated. Electroluminescence measurements on the dual-wavelength LED show a remarkable reduced blue shift in the emission wavelength with increasing the injection current, compared with that of the single-wavelength LEDs. This is attributed to the enhanced light emission from the red QWs with higher indium contents (deeper QWs). Additionally, photoluminescence measurements demonstrate that the red emission exhibits an increased luminescence intensity and higher thermal stability than the green emission when the temperature increased to room temperature. This study paves the avenue for improving the performance of the InGaN-based red LEDs by controlling the pre-strain in InGaN/GaN MQWs via stress engineering, thereby offering new perspectives for the design of high-quality long visible LEDs targeted for practical applications.